(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2010)
Since the introduction of the Bologna-system business administration training has changed a lot as it became the part of Hungarian language and literature BA training in the form of specialization. This combination is generated in the common linguistic roots of the two fields. Business administration specialization includes all the most important skills and competencies of this area, such as business communication, protocol, data processing, secretary skills, IT skills and of course students study touch-typing, shorthand-writing, reporting and text processing on a high level. We claim that about 40% of the graduated BA students wish to continue their studies in postgraduate courses. They can be employed by the media, public administration services and the competitive sector.